A Review of Students’ Common Misconceptions in Science and Their Diagnostic Assessment Tools - Soeharto, S.; Sarimanah, E.; Dewi, F. I.; Sabri, T.; Csapó, B. (Jurnal Pendidikan IPA Indonesia, 2019)
A misconception is well-known as a barrier to students in learning science. Some topics in science learning are always giving misconception to novice students, and there have been various kinds of diagnostic assessment used by researchers to identify student misconceptions in science. This present study provides information about an overview of the common topics that students usually get misconception in science, and diagnostic assessment used to identify students’ misconception in science. This review also provides a comparison of every instrument with the weaknesses and the strengths reviewed from a total 111 articles that had published from the year 2015 to 2019 in the leading journal having the topic of students’ misconceptions in science. This study revealed that 33 physics, 12 chemistry, and 15 biology concepts in science that mainly caused misconceptions to students. Furthermore, it found that interview (10.74%), simple multiple-choice tests (32.23%) and multiple tier tests (33.06%), and open-ended tests (23.97%) are commonly used as diagnostic tests. However, every kind of tests has benefits and drawbacks over the other when it is used in assessing student conception. An expert user like teachers and researchers must be aware when using diagnostic assessment in the learning process, exceptionally to construct student conception. This study is expected to help researchers and teachers to decide the best instrument to be used in assessing student misconceptions and to examine the common science topics that caused misconceptions.